2021
DOI: 10.3390/life11050392
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Resonance-Guided Focused Ultrasound in X-Linked Dystonia-Parkinsonism

Abstract: X-linked dystonia-parkinsonism (XDP) is a neurodegenerative condition found among males with maternal ancestry from Panay Island, Philippines. The treatment options are limited. We report on our experience of three XDP patients who underwent transcranial magnetic resonance-guided focused ultrasound (tcMRgFUS) pallidothalamic tractotomy. The three patients were all genetically confirmed XDP, with a mean XDP-Movement Disorder Society of the Philippines (MDSP) Scale score of 68.7/200. All patients were on stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…This was better than the reported outcome (30.1%) in a recent publication. 10 There was a significant improvement in our patient's pain sensation involving the right arm dystonia. In PD, the pain has been reported to be the only one that improved after pallidothalamic tractotomy.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This was better than the reported outcome (30.1%) in a recent publication. 10 There was a significant improvement in our patient's pain sensation involving the right arm dystonia. In PD, the pain has been reported to be the only one that improved after pallidothalamic tractotomy.…”
Section: Discussionmentioning
confidence: 55%
“…Only three patients with XDP have undergone unilateral tcMRgFUS. 10 Our patient underwent left pallidothalamic tractotomy. The PTT connects the globus pallidus internus with the ventroanterior/ventrolateral thalamus.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One patient presented mild dysarthria at 12 months and 3 reported dystonia recurrence. Anecdotally, three cases of genetically confirmed X-Linked Dystonia-Parkinsonism improved with ultrasound pallidothalamic tractotomy [53], and one case of genetically confirmed spinocerebellar ataxia showed a reduction of tremor after CTT ablation [54].…”
Section: Recent Developmentsmentioning
confidence: 99%
“…In addition to medication therapy, pallidal deep brain stimulation (DBS) surgery is a promising treatment for medically intractable primary dystonia, which involves the cortico–basal ganglia–thalamocortical motor loop in its pathogenesis [ 16 , 17 ]. Jamora et al showed the efficacy of lesioning the pallidothalamic tract using focused transcranial MR-guided ultrasound in dystonia patients with DYT3/XDP-TAF1, suggesting the involvement of the cortico–basal ganglia–thalamocortical loop in the pathogenesis of DYT3/XDP-TAF1 dystonia [ 18 ]. Goto et al proposed a striatal compartmental hypothesis in the pathogenesis of dystonia, which may affect the cortico–basal ganglia–thalamocortical loop [ 19 ].…”
mentioning
confidence: 99%